Concept of Hybrid Spirituality in the works of Paulo Coelho (International Journal of Food and Nutritional Sciences, 2022)
The present paper in an effort to understand the concept of hybrid spirituality and varied cultural dimensions in the works of Paulo Coelho. Spiritual aspects have always been a dominant feature in majority of Coelho's works. Paulo Coelho himself has become a synonym of spiritual genre among the contemporary readers. In most of his works the spiritual aspect is ignited, activated and adopted by the protagonists through a series of interconnected incidences which finally led to self-awareness. The multicultural background of Coelho had provided fertile ground for Coelho’s protagonist to establish, to understand and accept the diversified spiritual philosophies in different places. This Phenomenon of knowing ‘self’ through self-introspection along with the connection, understanding and restoration with the divine. Coelho himself had experienced this spiritual enlightenment which is the result of ‘multidimensional’ spiritual and cultural aspect which he had imbibed from his childhood in Brazil. The prismatic aspect of spirituality which Coelho projects in his work always made his readers connected to him across the boundaries. He discards the theory of spiritual globalization and believes that it is one’s spiritual responsibility to discover one’s spiritual zenith, which can be from any philosophy across the world, this captivating narration relish readers in the multidimensional spiritual spree which he creates.